Assessment of awareness regarding health hazards of plastic chemicals and their warning label among a sample population of Varanasi City: A cross-sectional study - Parul Sharma (Wolters Kluwer Medknow Publications, 2021)
Background: Plastic containers are widely used to store and serve edibles. In the production of some types of plastic, chemicals such as bisphenol A (BPA) and bisphenol S (BPS) are used. These chemicals leach from the plastic containers into the edibles, get access into the biological systems, and cause a toxic impact on health. Aim: This cross-sectional survey was planned to assess the usage of food contact plastic and awareness regarding the health hazards of plastic chemicals and warning labels on plastic items among a sample population of Varanasi city. Materials and Methods: Data were collected by interviewing the 556 adult participants, using a prevalidated structured questionnaire. Chi-square test was used to test the association and P < 0.05 was considered as significant. Results: Most of the participants were found to be following routine practices during cooking and storage of edibles which may expose them to BPA and BPS through the gut. Although many participants were aware that plastic may contain some type of chemicals which may enter the human body and harm human health in some way, they lacked precise knowledge regarding warning label like “BPA free plastic” “plastic containing BPA” and “food grade plastic.” Furthermore, none of the participants could recognize the “resin identification codes” correctly. Conclusion: Most of the participants had only elementary awareness of health risk of plastic usage. A significant number of participants lacked crucial information that can help them to make healthy choices as a consumer and use safe alternatives of plastic.